User interaction in Iraqi blended massive open online course model - Ali, Qusay Abboodi (2019)
Despite the evidence of Massive Open Online Course (MOOC) didactic values, most scholars do not emphasize user interaction (UI), user experience (UX), and MOOC design technique that accommodate the interrelated key components and design methods of MOOC based on different learners’ cultures and languages. As a result, there is a tendency to present MOOC as a challenging and impractical approach. Essentially, there is a lack of conceptual models and methods that comprehensively structure the crucial theories, components, techniques, technologies, and systematic processes of MOOC design. Within this context, this study proposes a blended MOOC (bMOOC) model in order to design, implement, and evaluate the Iraqi-bMOOC platform. To accomplish this, a number of sub-objectives are formed: (1) to determine the current limitations and challenges of MOOC in the higher education context from the perspective of Iraqi students, (2) to identify the design dimensions and components of a bMOOC model, (3) to construct and develop bMOOC model based on objective 2, and (4) to evaluate the user interaction of a bMOOC prototype based on the user experience. This study adopts the Design Science Research methodology as the framework of the research process. Activities of Iraqi-bMOOC model construction include a literature review, a comparative study and content analysis of the existing models, and an expert’s consultation. The proposed model is evaluated through an expert’s review, an experimental test, and user interaction. The results reveal that the majority of users are satisfied with the learning activities in the Iraqi-bMOOC platform. The results from the user interaction testing conclude that the proposed Iraqi-bMOOC model is perceived as significantly providing quality interactive learning as a blended learning resource for university students. This study also finds that the proposed model is well-accepted by the experts. Four major theoretical, practical, empirical, and educational contributions are obtained from this study: (i) collecting and analyzing the literature that has been conducted on MOOCs between 2008 and 2016 to get a deep and better understanding of the MOOC stakeholders and their behaviors, (ii) analytically providing a new understanding of the main components and criteria (Design Dimensions) of effective bMOOC environments that would be of value for developers to construct blended MOOC in the higher education context, (iii) increasing the interaction of Iraqi learners with the learning materials in a higher education environment via the Iraqi-bMOOC, and (iv) breaking down obstacles of traditional education and MOOC for anyone, anywhere, and anytime. In conclusion, it is hoped that this study does not only demonstrate the potential and impact of blended MOOC in technology-enhanced and student-centred learning, but it also provides a capstone for bMOOC research in the higher education context.